2021
DOI: 10.1099/ijsem.0.004970
|View full text |Cite
|
Sign up to set email alerts
|

Nocardia huaxiensis sp. nov., an actinomycete isolated from human skin

Abstract: A novel actinomycete, designated as strain WCH-YHL-001T, was isolated from skin biopsy specimens of a patient at West China Hospital, Chengdu, Sichuan Province, PR China. The cells were Gram-positive, aerobic, heterotrophic and non-motile. They formed an extensive substrate with short aerial mycelia, whose branches fragmented into rod-shaped elements. Growth occurred at 10–40 °C, pH 5.0–12.0 and with NaCl concentrations of 0–4.0 % (w/v). The major cellular fatty acids of strain WCH-YHL-001T were C16 : 0, C18 :… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…We extracted the whole 16S rRNA sequence from the assemble genome and fount it showed the highest similarities (99.93%) with the 16S rRNA sequence of the strain Nocardia huaxiensis WCH-YHL-001 T . We further compared the Average Nucleotide Identity (ANI) of the two strains and found that the ANI value was determined of 99.47%, indicating that the strain belong to a novel Nocardia species, N. huaxiensis , whose phylogenetic analysis was performed based on the 16S rRNA sequence ( 10 ). However, some reports have confirmed that the 16S rRNA sequence cannot provide enough genetic information to distinguish between closely-related species ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We extracted the whole 16S rRNA sequence from the assemble genome and fount it showed the highest similarities (99.93%) with the 16S rRNA sequence of the strain Nocardia huaxiensis WCH-YHL-001 T . We further compared the Average Nucleotide Identity (ANI) of the two strains and found that the ANI value was determined of 99.47%, indicating that the strain belong to a novel Nocardia species, N. huaxiensis , whose phylogenetic analysis was performed based on the 16S rRNA sequence ( 10 ). However, some reports have confirmed that the 16S rRNA sequence cannot provide enough genetic information to distinguish between closely-related species ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nocardia huaxiensis ( N.huaxiensis ) was first isolated from skin biopsy specimens of a patient and identified as a novel Nocardia species in 2021 ( 10 ). There was no other reported case of human infection caused by this species.…”
Section: Introductionmentioning
confidence: 99%
“…The cells were harvested by centrifugation, washed twice with distilled water, recentrifuged and freeze-dried. The freeze-dried cell biomass was used to analyze polar lipids, quinones and cell sugars at the Guangdong Institute of Microbiology (Guangzhou, Guangdong, PR China), as described by Wu et al [ 23 ] and Zhuang et al [ 24 ].…”
Section: Physiological and Chemotaxonomic Analysismentioning
confidence: 99%
“…Forty-eight BALB/C mice were divided into 4 groups: high-dose infection group (7.0 x10 7 cfu/mL, n = 12), low-dose infection group (3.5 x10 6 cfu/mL, n = 12), immunosuppressed group (n = 12), and control group (n = 12). The mice in the infection and immunosuppressed groups were intraperitoneally injected with 150 mg/kg cyclophosphamide on days −3, −1, and +1 relative to infection, as in another study [ 24 ]. The experimental mice in the infection group were administered 50 µL of bacterial culture solution via nasal drip on day 0, and 50 µL of phosphate-buffered saline was administered to the mice in the immunosuppressed and control groups.…”
Section: Bacterial Pathogenicity In Vivomentioning
confidence: 99%
“…A biopsy specimen smear showed Gram‐positive rods with branching filaments (b). The corresponding culture recovered Nocardia species (c), finally identified by whole‐genome sequencing as a novel species, Nocardia huaxiensis 1 . N .…”
mentioning
confidence: 99%